New sources of sorghum resistant genotypes to downy mildew disease in Uganda (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Kumi F, Badji A, Mwila N, Odong T, Ochwo-Ssemakula M, Tusiime G, Gibson P, Biruma M, Prom KL, Cuevas HE, Agbahoungba S, Rubaihayo P. 2019. New sources of sorghum resistant genotypes to downy mildew disease in Uganda. Biodiversitas 20: 3391-3397.  Sorghum downy mildew (SDM) disease is still prevalent in Uganda at varying levels of incidence and severity. In this study, a total of 100 sorghum genotypes, five (5) from (U.SA, India, and Sudan) and 95 genotypes from Uganda were evaluated for resistance to downy mildew and other agronomic traits during the second growing season of 2016 (August-December). The experiment was conducted in two locations at Makerere University Agricultural Research Institute at Kabanyolo (MUARIK) and Abi-Zonal Agricultural Research and Development Institute (Abi-ZARDI) research station at Arua. The experimental design used was 10 x 10 alpha lattice design with three replicates. Data were collected on plant disease incidence (PDI), plant disease severity (PDS), area under disease progress curve (AUDPC), days to 50% flowering, plant height, 1000 seed weight, and grain yield. Results for analysis of variance showed highly significant differences (P < 0.001) in genotypes, location, and AUDPC, yield and yield components. Disease incidence varied significantly (P < 0.001) between locations, and Arua recorded highest disease incidence and severity of 80.6 and 2.8, respectively. Results from correlation analysis showed a highly significant (P < 0.001) positive association of downy mildew disease incidence with AUDPC (0.835) which suggests that the severity of SDM disease increased with disease incidence, whiles significant (P < 0.001) negative correlation was recorded for days to 50 % flowering (-0.302), 1000 seed weight (-0.471), and grain yield (-0.585), suggesting that grain yield and yield component decreased significantly with increase in SDM incidence and severity. Two resistant (PI 656061 and PI 533831) and four moderately resistant (E 40, MAKSO 8, PI 655990 and Epuripur) genotypes were identified from this study. These genotypes were recommended for sorghum breeding program against downy mildew disease.
Keywords: Angle transformation, AUDPC, PDI, local lesions, systemic infection